Pengembangan Media Smart Box Aku Cinta Pancasila pada Siswa Kelas I Sekolah Dasar - Ela Aidia; Iqnatia Alfiansyah; Ismail Marzuki (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to (1) describe the process of developing the Smart Box Aku Cinta Pancasila learning media for first-grade elementary school students, (2) describe the validity of the Smart Box Aku Cinta Pancasila learning media, and (3) describe students’ responses to the Smart Box Aku Cinta Pancasila learning media. This research is a developmental study using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The study was conducted at UPT SD Negeri 253 Gresik during the odd semester. The research subjects consisted of 25 students, comprising 10 male students and 15 female students. The data collection techniques included interviews, media expert validation questionnaires, material expert validation questionnaires, learning outcomes test and student response questionnaires. The results of the study indicate that the Smart Box Aku Cinta Pancasila learning media obtained a media expert validation score of 96,25% with a very valid category, a material expert validation score of 97,50% with a very valid category, and a student response score of 97,2% with a very good category. Based on these results, the Smart Box Aku Cinta Pancasila learning media is considered valid and get a positive response, and therefore suitable for use as a learning media for Pancasila Education for first-grade elementary school students.